Growth hormone and erythropoietin differentially activate DNA-binding proteins by tyrosine phosphorylation. - Finbloom, D S (1994)
Binding of growth hormone (GH) and erythropoietin (EPO) to their respective receptors results in receptor clustering and activation of tyrosine kinases that initiate a cascade of events resulting not only in the rapid tyrosine phosphorylation of several proteins but also in the induction of early-response genes. In this report, we show that GH and EPO induce the tyrosine phosphorylation of cellular proteins with molecular masses of 93 kDa and of 91 and 84 kDa, respectively, and that these proteins form DNA-binding complexes which recognize an enhancer that has features in common with several rapidly induced genes such as c-fos. Assembly of the protein complexes required tyrosine phosphorylation, which occurred within minutes after addition of ligand. The activated complexes translocated from the cytoplasm to the nucleus. The protein activated by GH is antigenically similar to p91, a protein common to several transcription complexes that are activated by interferons and other cytokines. In contrast, the proteins activated by EPO are distinct from p91. These findings establish the outlines for a cytokine-induced intracellular signaling pathway, which begins with ligand-induced receptor clustering that activates one or more tyrosine kinases. These data are the first to demonstrate that GH- and EPO-activated tyrosine-phosphorylated proteins can specifically recognize a well-defined enhancer and therefore provide a mechanism for rapidly transducing signals from the membrane to the nucleus.